Review of in-situ process monitoring and in-situ metrology for metal additive manufacturing - Everton, Sarah K.; Hirsch, Matthias; Stravroulakis, Petros; Leach, Richard K.; Clare, Adam T. (Elsevier, 2016)
Lack of assurance of quality with additively manufactured (AM) parts is a key technological barrier that prevents manufacturers from adopting AM technologies, especially for high-value applications where component failure cannot be tolerated. Developments in process control have allowed significant enhancement of AM techniques and marked improvements in surface roughness and material properties, along with a reduction in inter-build variation and the occurrence of embedded material discontinuities. As a result, the exploitation of AM processes continues to accelerate. Unlike established subtractive processes, where in-process monitoring is now commonplace, factory-ready AM processes have not yet incorporated monitoring technologies that allow discontinuities to be detected in process. Researchers have investigated new forms of instrumentation and adaptive approaches which, when integrated, will allow further enhancement to the assurance that can be offered when producing AM components. The state-of-the-art with respect to inspection methodologies compatible with AM processes is explored here. Their suitability for the inspection and identification of typical material discontinuities and failure modes is discussed with the intention of identifying new avenues for research and proposing approaches to integration into future generations of AM systems.